Adverse Effects Post COVID-19 Vaccination and its Association with Age, Gender and Comorbid Disease in Basrah City Southern of Iraq - Abdul-Nabi, Zainab N.; Mohamed-Jawad, Noor Kadhim; Fareed, Noor Yousif; Neamah, Nadheerah Falih; Shari, Falah Hassan (Current Drug Safety, 2024)
Background: Vaccination against COVID-19 virus is the most valuable tool available for protection during the pandemic of coronavirus. The clinical manifestation post-vaccination is a barrier to vaccination for many people in Iraq and worldwide.Objectives: The objective of this study is identifying various clinical manifestations occurring after receiving vaccines among individuals in Basrah Governorate. Moreover, we examine its association with respondents' demographics and the type of vaccine they received.Methods: A cross-section study was conducted in Basrah, southern Iraq. Research data were collected through an online questionnaire. The data were analyzed using both descriptive and analytic statistical tools using the SPSS program.Results: Most of the participants (86.68%) received the vaccine. The side effects were reported in 71.61% of vaccinated individuals. Fever and muscle pain were the two most experienced clinical manifestations, while lymph node enlargement and disturbances in taste and/or smell sensations were reported infrequently. Adverse effects were mostly reported with the Pfizer BioNTech vaccine receiver. Females and those in the younger age group also reported a significantly higher incidence of side effects.Conclusion: Most adverse effects related to the COVID-19 vaccine were minor and could be tolerated without the need for hospital admission.
Keywords: comorbidity